Impact of Semi-Fowler Position and Clapping in Oxygen Saturation in COPD Patients - Dinaryanti, Ratna Sari; Yulefsi, Besmina; Malkis, Yenni; Fitriani, Rina; Wasijati, Wasijati (Universitas Airlangga, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) is a non-communicable disease that often causes low oxygen levels and shortness of breath. The semi-Fowler position and clapping are non-pharmacological techniques that help improve lung function and clear mucus. This study aims to determine their effect on increasing oxygen saturation in COPD patients. Methods: This experimental study included 18 COPD patients in the Hospital Care Unit (HCU), selected through consecutive sampling. Inclusion criteria were diagnosed COPD, conscious patients willing to participate, and oxygen saturation below 90%. Exclusion criteria included hemodynamic instability. The intervention involved placing patients in a semi-Fowler position (45° incline) to enhance lung expansion and performing clapping (gently tapping the chest with cupped hands) to aid mucus clearance. Oxygen saturation was measured before and after using a pulse oximeter. The Wilcoxon Signed-Rank Test was used to analyze non-normally distributed data. Results: The mean oxygen saturation before intervention was 85.94%, increasing to 98.56% post-intervention, with a significant improvement of 12.62% (p=0.00, p < 0.05). Demographic data, including age, gender, and COPD severity, were collected. Conclusion: The semi-Fowler position and clapping significantly improve oxygen saturation in COPD patients, highlighting their clinical usefulness. Future research should explore long-term effects, different COPD severities, and combinations with other respiratory therapies for better disease management.